Test of 8-hydroquinoline copper against Neopestalotiopsis thailandica in the greenhouse and budwood garden on Rubber Plant (Hevea brasiliensis) - Febbiyanti Tri Rapani; Matsui Minami (BIO Web of Conferences)
Pestalotiopsis leaf fall disease is the most important disease in rubber plants currently because it has become an outbreak and results in yield losses of up to 40%. One way to control this disease is to use chemical fungicides which work quickly and are able to suppress disease development more effectively. Therefore, research is necessary regarding the effect of the chemicals 8 Hydroquinone copper in inhibiting growth Neopestalotiopsis thailandica in the laboratory and greenhouse on polybag seeds. The aim of this research purposes to determine the efficacy test of 8-hydroquinoline copper against Neopestalotiopsis thailandica in the greenhouse and budwood garden on Rubber Plant (Hevea brasiliensis). Greenhouse test results showed that 8-hydroquinoline copper at a dose of 400 ppm was able to suppress the development of Pestalotiopsis, and 800 ppm provided the best suppression of disease development in rubber plant seedlings in the greenhouse and results at Budwood Garden showed that 8-hydroquinone copper was able to suppress the Pestalotiopsis LFD compared to other chemical fungicides.